2022
DOI: 10.2174/1871530321666210125125500
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of HCV Eradication after Direct-Acting Antiviral Agents on Hepatic Steatosis: A Prospective Observational Study

Abstract: Background and Aims: Eradication of hepatitis C virus (HCV) by direct-acting-antiviral-agents (DAAs) was followed by fibrosis regression, but little is available about hepatic steatosis changes after DAAs. The aim of this work was to assess the prevalence of hepatic steatosis among HCV Egyptian patients and the long term changes occur after viral eradication. Methods: This prospective cohort study included 150 HCV patients with significant fibrosis. They were examined by Transient elastography to evaluate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…10 Treatment with DAAs reduces liver stiffness; however, this is negatively associated with an increase in the severity of fatty liver. 77,78 Co-existing fatty liver is also a risk factor for Kawaguchi T et al P. 8 HCC after cure in patients with HCV infection. 79,80 Furthermore, Peleg et al demonstrated that fatty liver is a major predictor of all-cause mortality in patients who achieve a sustained virological response following DAA treatment, regardless of fibrosis stage.…”
Section: Importance Of Multiple Etiologies Of Liver Disease: Mafld Viral Hepatitis and Alcoholic Intakementioning
confidence: 99%
See 1 more Smart Citation
“…10 Treatment with DAAs reduces liver stiffness; however, this is negatively associated with an increase in the severity of fatty liver. 77,78 Co-existing fatty liver is also a risk factor for Kawaguchi T et al P. 8 HCC after cure in patients with HCV infection. 79,80 Furthermore, Peleg et al demonstrated that fatty liver is a major predictor of all-cause mortality in patients who achieve a sustained virological response following DAA treatment, regardless of fibrosis stage.…”
Section: Importance Of Multiple Etiologies Of Liver Disease: Mafld Viral Hepatitis and Alcoholic Intakementioning
confidence: 99%
“…In patients with HCV infection, DAAs are currently the standard of care and achieve high cure rates in real-world settings [ 10 ]. Treatment with DAAs reduces liver stiffness; however, this is negatively associated with an increase in the severity of fatty liver [ 77 , 78 ]. Co-existing fatty liver is also a risk factor for HCC after cure in patients with HCV infection [ 79 , 80 ].…”
Section: Importance Of Multiple Etiologies Of Liver Disease: Mafld Vi...mentioning
confidence: 99%
“…В научной литературе данные о динамике стеатоза печени после достижения УВО противоречивы. Часть из них демонстрирует уменьшение САР ТМ по данным ТФ, в том числе и у пациентов с ЦП, через 12-24 недели после окончания терапии ПППД [32][33][34][35], другие, наоборот, прогрессию стеатоза печени [36][37][38]. В проведенном исследовании зарегистрирована высокая распространенность стеатоза печени как до начала ПВТ, так и при длительном мониторинге после достижения УВО.…”
Section: Discussionunclassified
“…In addition, persistence and even an increase in the degree of steatosis are observed in patients who achieve a Sustained Virologic Response (SVR) after specific treatment with Direct-Acting Antiviral (DAA) drugs one year after treatment ends. 5 , 6 , 7 Interestingly, diabetes mellitus was reported to be a factor that independently affected liver stiffness after DAA treatment despite SVR. 8 The underlying mechanisms involving the presence of steatosis, especially before treatment, can be alcohol consumption, being overweight, obesity, diabetes type 2 mellitus, HCV genotype, Human Immunodeficiency Virus (HIV) coinfection, and genetic polymorphisms in genes, such as Transmembrane six Superfamily member 2 ( TM6SF2 ), Patatin-Like Phospholipase Domain Containing 3 ( PNPLA3 ) and Microsomal Triglyceride Transfer Protein ( MTTP ).…”
Section: Introductionmentioning
confidence: 99%